2006
DOI: 10.1051/0004-6361:200600018
|View full text |Cite
|
Sign up to set email alerts
|

Observation of kink waves in solar spicules

Abstract: Height series of Hα spectra in solar limb spicules obtained with the 53 cm coronagraph of the Abastumani Astrophysical Observatory are analyzed. Each height series covered 8 different heights beginning at 3800 km above the photosphere. The spatial difference between neighboring heights was 1 , consequently ∼3800−8700 km distance above the photosphere has been covered. The total time duration of each height series was 7 s. We found that nearly 20% of measured height series show a periodic spatial distribution o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 18 publications
4
68
0
Order By: Relevance
“…A cadence of ∼7.7 s limits the maximum phase speed that may be detected to ∼130 km s −1 . The mean period, amplitude, and phase speed of the observed oscillations are similar to results found for limb spicules (Kukhianidze et al 2006;Zaqarashvili et al 2007;Kim et al 2008;He et al 2009b;Okamoto & de Pontieu 2011).…”
Section: Analysis and Discussionsupporting
confidence: 85%
“…A cadence of ∼7.7 s limits the maximum phase speed that may be detected to ∼130 km s −1 . The mean period, amplitude, and phase speed of the observed oscillations are similar to results found for limb spicules (Kukhianidze et al 2006;Zaqarashvili et al 2007;Kim et al 2008;He et al 2009b;Okamoto & de Pontieu 2011).…”
Section: Analysis and Discussionsupporting
confidence: 85%
“…The bulk (shear) Alfvén waves only exist in a homogeneous medium (Nakariakov & Verwichte 2005;Goossens et al 2013), that is likely not the case in the solar atmosphere. The SCFs are possibly a manifestation of plasma jets along horizontal flux tubes, thus, according to the MHD wave theory, the kink mode is the most appropriate interpretation of their swaying motions (Kukhianidze et al 2006;Erdélyi & Fedun 2007;Zaqarashvili et al 2007). Note, however, that the fact that brightenings along the fibrils start more often inside the bulk of the fibrils than at one of their edges speaks against the interpretation of the fibrils as plasma jets.…”
Section: The Structures Listed Inmentioning
confidence: 99%
“…Giovanelli (1975), e.g., describes waves along Hα mottles and fibrils with speeds of 70 km s −1 and interprets them as Alfvén waves in magnetic flux tubes with approximately 10 Gauss field strength. Kukhianidze et al (2006), from time sequences in Hα off the limb, found kink waves in spicules with periods of 35−70 s. Hansteen et al (2006) and Rouppe van der Voort et al (2007) observed spicules and fibrils in the quiet Sun and in active regions with high spatial and temporal resolution observations. They succeeded via numerical simulations in explaining the dynamics of these chromospheric small-scale structures by magnetoacoustic shocks, excited mainly by the solar 5-min oscillations (see also the simulations by Sterling & Hollweg 1989; and the review by Carlsson & Hansteen 2005).…”
Section: Introductionmentioning
confidence: 99%